2017
DOI: 10.1057/sj.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

The when and where of an emerging crime type: The example of metal theft from the railway network of Great Britain

Abstract: Metal theft has become an increasingly common crime in recent years, but lack of data has limited research into it. The present study used police-recorded crime data to study the spatial and temporal concentration of metal theft from the railway network of Great Britain. Metal theft was found to exhibit only weak seasonality, to be concentrated at night and to cluster in a few locations close to -but not in -major cities. Repeat-victimisation risk continued for longer than has been found for other crime types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Such concentrations of people in contained environments make the systems especially vulnerable to attack through the use of explosives and improved explosive devices (Ashby et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such concentrations of people in contained environments make the systems especially vulnerable to attack through the use of explosives and improved explosive devices (Ashby et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This allowed the study to programmatically replicate the method that BTP officers use to determine at which station the crime should be recorded as having happened. The distance from a feature to the nearest line was considered to be more important than the distance to the nearest station, since it is from the line-side that most metal is stolen (Ashby, Bowers, Borrion, & Fujiyama, 2014).…”
Section: Datamentioning
confidence: 99%
“…Finally, metal theft is, generally, unlike most other property crimes, making it difficult to take existing taxonomies and apply them to this area of study. Ashby et al (2014) concluded in their study of metal theft from the railway network of Great Britain that metal thefts may more likely be planned rather than opportunistic. They also suggested that, "more certain and more detailed results on the extent to which metal thieves plan their offending could be obtained using alternative methods such as offender interviews" (p. 18).…”
Section: Drug Hyperbole Conclusion It Is Doubtful That a Firm Connecmentioning
confidence: 99%
“…As discussed in the taxonomy section, various researchers and authors believe (or at least identify) metal thieves as behaving in a rational manner (Ashby et al, 2014;Bennett, 2008b;Posick et al, 2011;Sidebottom et al, 2011Sidebottom et al, , 2014. Moreover, many metal thieves demonstrate significant knowledge, organization, skill and self-control to complete their thefts.…”
Section: Theories: Rational Choice and Routine Activitiesmentioning
confidence: 99%
See 1 more Smart Citation